2017
DOI: 10.1002/lary.26531
|View full text |Cite
|
Sign up to set email alerts
|

Compound motor action potential duration and latency are markers of recurrent laryngeal nerve injury

Abstract: NA. Laryngoscope, 127:1855-1860, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Compound nerve action potential (CNAP) duration, an index of conduction in nerve bundles 26 was measured by a stimulus electrode placed at distance greater than 3 mm from a bipolar sensing electrode in differential amplifier mode with electrode spacing at 2 mm (2x10 -3 m). The common ground for the bipolar sensing electrode and stimulation electrode were placed in the foot of the mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Compound nerve action potential (CNAP) duration, an index of conduction in nerve bundles 26 was measured by a stimulus electrode placed at distance greater than 3 mm from a bipolar sensing electrode in differential amplifier mode with electrode spacing at 2 mm (2x10 -3 m). The common ground for the bipolar sensing electrode and stimulation electrode were placed in the foot of the mouse.…”
Section: Methodsmentioning
confidence: 99%
“…There was also a significant correlation between CMAP latency and FP/HP BoS, which in our opinion has to be interpreted with great caution. One could hypothesize that CMAP latency might serve as a surrogate marker for the conductance velocity of sensory fibers as well (Bhatt et al, 2017); therefore, an increase in latency could correspond to a slower conductance velocity of sensory afferents. As slower conductance of sensory afferents might correspond to slower recovery of sensory perception and Print Area in consequence, this might serve as an explanation for the observed degree of correlation, given our consideration of how BoS is affected by Print Area.…”
Section: Correlation Of Outcome Measuresmentioning
confidence: 99%
“…18 Previous work has demonstrated that millimeters of electrode adjustment can dramatically affect the CMAP amplitude. 15,16 Future studies should investigate methods to most accurately place the receiving needle electrode. Should the needle electrode technique ultimately prove to be nonreproducible, alternative options including surface electrodes, 28 macro electromyography needles, 29 or hook wire electrodes may need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…13 Given the widespread use of NCSs in other neuropathies, this measure may have clinical utility as an objective measure of laryngeal innervation. Previously published animal studies demonstrate that laryngeal NCSs can quantify acute changes in laryngeal innervation, 14 measure changes in compound motor action potential (CMAP) duration and latency, 15 and quantify the degree of nerve recovery after specific RLN injuries. 16 These studies were performed in anesthetized animals after the RLN was surgically dissected and directly stimulated.…”
Section: Introductionmentioning
confidence: 99%